Encyclopedia of human emotions - Levinson, David 1947-.; Ponzetti, James J.; Jorgensen, Peter F. (New York Macmillan Reference USA, 1999)
"Why do people cry, how do we manage horror, what do facial expressions tell us about a person? The answers to these questions and many more can be found in the Encyclopedia of Human Emotions, which brings to gether what is known about the nature, causes, expressions, and societal role of emotions. The 146 alphabetically arranged articles are sprinkled with photos, illustrations, and references to literature. Also covered are biographies, emotions that have been the subject of scientific study, and how emotions relate to society (e.g., hate crimes). The plain language of this unique encyclopedia makes it accessible to high-school students and the general user, while the level of scholarship makes this a useful resource to researchers as well."--"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
v. 1. A-H -- v. 2. I-Z, Index.
UCWS-2014-G-1827 v. 2 donated by Sandra Repulda Gonzales
Keywords: Emotions -- Encyclopedias; Affect (Psychology) -- Encyclopedias; Mood (Psychology) -- Encyclopedias